Cardiac cycle: an observational/interventional study protocol to characterise cardiopulmonary function and evaluate a home-based cycling program in children and adolescents born extremely preterm - Jeanie L Y Cheong; Michael M H Cheung; Melanie M Clarke; Jonathan P Mynard; Claire E Willis (BMJ Open)
Introduction Extremely preterm (EP)/extremely low birthweight (ELBW) individuals may have an increased risk for adverse cardiovascular outcomes. Compared with term-born controls, these individuals have poorer lung function and reduced exercise capacity. Exercise interventions play an important role in reducing cardiopulmonary risk, however their use in EP/ELBW cohorts is unknown. This study, cardiac cycle, aims to characterise the cardiopulmonary system of children and adolescents who were born EP compared with those born at term, following acute and chronic exercise bouts.Methods and analysis The single-centre study comprises a home-based exercise intervention, with physiological characterisation at baseline and after completion of the intervention. Fifty-eight children and adolescents aged 10–18 years who were born EP and/or with ELBW will be recruited. Cardiopulmonary function assessed via measures of blood pressure, arterial stiffness, capillary density, peak oxygen consumption, lung clearance indexes and ventricular structure/function, will be compared with 58 age-matched and sex-matched term-born controls at baseline and post intervention. The intervention will consist of a 10-week stationary cycling programme, utilising Zwift technology.Ethics and dissemination The study is approved by the Ethics Committee of the Royal Children’s Hospital Melbourne under HREC2019.053. Results will be disseminated via peer-reviewed journal regardless of outcome.Trial registration number 12619000539134, ANZCTR